Pengaruh Gaya Kepemimpinan Terhadap Kualitas Kehidupan Kerja Karyawan Perum Pegadaian Kantor Pusat Wilayah V Manado - Jensenem, Manfred B; Sambul, Sofia M (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: The purpose of this study to determine the effect on Quality of Life Leadership Styles on Employees' Pawnshop Regional Office V Manado. This study uses a quantitative approach to the type of research that emphasizes the statistical analysis. Variables examined in this study consists of two variables, namely: (1). leadership style as an independent variable and (2) Quality of Work Life as a dependent variable. The results showed that the effect of leadership styles on employees' quality of work life in Pawnshop Regional Office V Manado. The results of this research can be used as information for particular Pawnshop Pawnshop Headquarters Manado Region V, to know the things that should get attention, or to be a priority to improve the quality of working life of employees, as well as trying to better understand the needs of employees in the work . Keywords: Leadership, Leadership Style, Quality of Work Life